The usefulness of transient elastography in the assessment of patients with HBeAg‐negative chronic hepatitis B virus infection. Issue 7 (6th October 2013) - Papatheodoridis, G. V.; Manolakopoulos, S.; Margariti, A.; Papageorgiou, M. V.; Kranidioti, H.; Katoglou, A.; Kontos, G.; Adamidi, S.; Kafiri, G.; Deutsch, M.; Pectasides, D.
Summary Histological severity is often mandatory for the management of HBeAg‐negative chronic HBV patients. We evaluated the performance of transient elastography (TE) in this setting. We included 357 untreated HBeAg‐negative patients with ≥1 reliable liver stiffness measurement (LSM‐kPa) by TE: 182 inactive carriers with HBV‐DNA < 2000 (n = 139) or 2000–19 999 IU/mL (n = 43) and 175 patients with chronic hepatitis B (CHB). In carriers, HBV‐DNA > 2000 and/or LSM > 6.5 were considered as biopsy indications. LSMs did not differ between carriers with low and high viremia, but were lower in carriers than in patients with CHB (5.8 ± 1.7 vs 9.0 ± 5.6, P < 0.001) offering moderate differentiation between these two groups (AUROC: 0.705). LSMs did not change significantly in carriers after 16 (12–24) months. In carriers with a liver biopsy, Ishak's staging scores were similar between cased with low and high viremia but higher in cases with LSM > 6.5 than ≤6.5 kPa. Moderate fibrosis (stages: 2–3) was detected in 0/10 carriers with only HBV‐DNA > 2000 IU/mL, 2/10 (20%) carriers with only LSM > 6.5 and 5/10 (50%) carriers with both HBV‐DNA > 2000 and LSM > 6.5 (P = 0.009). In patients with CHB, LSMs correlated significantly with grading and staging scores and offered excellent accuracy for ≥moderate, ≥severe fibrosis or cirrhosis (AUROC ≥ 0.919–0.950). TE can be helpful for the noninvasive assessment of HBeAg‐negative chronic HBV patients. In conclusion, LSMs offer excellent accuracy for fibrosis severity in HBeAg‐negative patients with CHB and can identify carriers with high risk of moderate fibrosis, which may be present in up to 35% of carriers with LSM > 6.5 kPa and 50% of carriers with LSM > 6.5 kPa and HBV‐DNA > 2000 IU/mL.